KAJIAN HUKUM KEHARUSAN BAGI NOTARIS DAN PPAT YANG MERANGKAP JABATAN BERKEDUDUKAN DALAM SATU DAERAH ATAU WILAYAH KERJA - Raden Hamengku Aji Dewondaru; Umar Ma’ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
View the establishment of notary formation and PPAT that have been set Based on their respective authorities, it appears that a notary can Concurrent PPAT as long as in one working area within the territory of office Notary Public. This is the author's interest to study about duplicate Position, because it does not close the possibility will happen Dual positions between Notary and PPAT which not one office but still One area of notary public. So this discourse needs to be studied in order to be able Known the possible impact that will appear.The formulation of the problem in this research are: 1.) Why are there any provisions that require notary work area / region and PPAT in one area / work area? 2.) What are the consequences or sanctions faced by a notary who holds PPAT if it is not domiciled in one territory / Working Area and 3.) What is the action done by the Honorary Assembly if the notary concurrent with PPAT is not domiciled in the same work area. The method used in this research is the normative juridical approach, the type of normative legal research. The source of the data is the secondary data. Technique of collecting data with bibliography, method of analysis by using method of qualitative data analysis. Problems are analyzed with the theory of benefit and the theory of justiceBased on the result of this research, it can be concluded 1.) Reason requiring Regional / Working Areas of Notary and PPAT in One Region / Working Area is in accordance with the Law on Notary Position and Government Regulation Number 37 Year 1998 About PPAT Regulation. 2.) Result or sanction faced by a Notary who concurrently PPAT if not domiciled in one region / work area. Legal effect to Notary Deed, the deed is null and void or can be canceled. Notary deed may be canceled because if there is a lawsuit from the parties mentioned in the deed to cancel notary deed and Legal Effect on Notary's Office. 3.) Acts Conducted by Honorary Council If Notary Accepting PPAT Not Domiciled In The Same Working Area gives warning and witness or revocation of permit. Keywords: Multiple Position, Region / Working Area, Notary and PPAT